Field Performance of TC1507 Transgenic Corn Hybrids Against Asian Corn Borer in the Philippines - Thompson, G. D. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2010)
Two TC1507 transgenic Bt corn hybrids with the cry1F gene, their conventional isogenic hybrids and a conventional local hybrid were planted in five locations in 2006 wet season and seven locations in 2006–2007 dry season, to evaluate their performance against the Asian corn borer (ACB), Ostrinia furnacalis Guenée, as part of the Dow AgroSciences regulatory field trials to gain approval for cultivation of this corn hybrid in the Philippines. The two TC1507 hybrids had 0.00–0.14 tunnels per plant while the conventional isogenic hybrids averaged 1.08–9.51 tunnels per plant. More tunnels were observed on the two non-Bt isogenic hybrids and the conventional local hybrid during the wet season than during the dry season. Damage also varied with location. The TC1507 event was highly effective against ACB and provided significant yield benefits over the conventional corn hybrids, particularly under severe ACB infestation. TC1507 had reduced number of borer tunnels (99.1%), foliar injury (84.2%), total tunnel length per plant (99.9%) and averaged 2.08 mt more per ha yield than the non-Bt isogenic hybrids across the 12 test locations. Implication of TC1507 transgenic Bt corn in ACB resistance management is discussed.